Study of SWCNTs-Supported Pd and Pt Catalyst by K Filled - Cao, You-Ming (Asian Journal of Chemistry, 2013)
In order to improve reducing property of single-walled carbon nanotubes, potassium was filled in interior of carbon nanotubes on vacuum condition. Single-walled carbon nanotubes-supported Pt and Pd catalyst was obtained when potassium filled single-walled carbon nanotubes was put in K2PtCl6 and PdCl2 solution. The as-grown products were characterized using transmission electron microscopy, X-ray photoelectron spectroscopy techniques and mechanism of potassium filled single-walled carbon nanotubes supporting metal was researched. The results showed that potassium filled single-walled carbon nanotubes is better than the single-walled carbon nanotubes in terms of the reducing property, capacity and particle size (particles with diameters of 1 nm) of supporting metal. Potassium filled single-walled carbon nanotubes-supported Pt and Pd has good performance on distribute, tight and purity. From the research of electron transfer, electron move from potassium to the surface of single-walled carbon nanotubes. Subsequently, metal ion obtained electron was deposited on the surface of single-walled carbon nanotubes. Solution reached neutral between potassium ion and anion.